KEWENANGAN PEMERINTAH DAERAH DALAM PENGUASAAN ATAS TANAH - Santoso, Urip (Jurnal Dinamika Hukum, 2013)
Tenure of land that can be controlled by local government is the Right to Use and Right Management of Land. Local government authority of the land with the status of Right to Use is the use of land for the benefit of its duties. If the land statutes Right Management of Land, the authority is planning designation and land use, land use for the benefit of its operation, and handed the parts of Right Management of Land to third parties and/or work with third parties. Local government are not authorized to lease land Right to Use and their Right Management of land to another party.Key words: authority, local government, tenure of land